2020
DOI: 10.31578/jebs.v6i1.217
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Out-of-Class Language Activities on English as a Foreign Language Proficiency of Private University Students - (A Case of Erbil)

Abstract: Abstract The present study aims at revealing the impact of engagement in out-of-class learning on foreign language students’ language proficiency. Accordingly, the relationship of private university EFL students’ involvement in English language activities outside the classroom with their language proficiency is investigated. The researcher designed a study based on descriptive quantitative research method utilizing a questionnaire comprising 25 items and administered it to the freshmen from English langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The study's main findings revealed that students' autonomy and classroom interaction were positively associated and that also supports the existence of autonomy in schools. On the other hand, this study comes in agreement with [15] who made a study about out-of-class language activities and concluded that the most common activities in which English is used are enjoyable activities such as watching movies, videos, and surfing the Internet, and that students' involvement in English language activities outside of the classroom is required a kind of language proficiency. This result is justifiable specifically if it is related to young learners.…”
Section: Resultssupporting
confidence: 86%
“…The study's main findings revealed that students' autonomy and classroom interaction were positively associated and that also supports the existence of autonomy in schools. On the other hand, this study comes in agreement with [15] who made a study about out-of-class language activities and concluded that the most common activities in which English is used are enjoyable activities such as watching movies, videos, and surfing the Internet, and that students' involvement in English language activities outside of the classroom is required a kind of language proficiency. This result is justifiable specifically if it is related to young learners.…”
Section: Resultssupporting
confidence: 86%
“…According to academic staff and university administrators, 52 percent of students are not involved in the educational process, while 6.5 percent say students are sufficiently active, according to a KRI study (Atrushi & Woodfield, 2018). Bala (2020) revealed in her research that physics education department students obtained the highest language proficiency mean scores with M=2.33 and also they participate into the activities outside the classroom with M=3.29 more than the students from other departments. The mean scores of the activity participation both in-class and out-class are not satisfactory considering the nature of learning at university level.…”
Section: The Results Of Subscales In Laq Of U1 U2 and U3mentioning
confidence: 99%
“…According to Sundqvist (2009), Extramural English interaction is not initiated by the teacher or anyone but the initiative of the students themselves, sometimes they can be influenced by other people, such as friends, educational influencers, or parents. As stated by Bala (2020), Extramural English activity is the involvement of English outside of learning in class or in students' free time, and not as an obligation to do it like homework in general. Some Extramural English activities according to Sundqvist (2009) include television (TV) programs, movies, music videos, or video blogs (vlogs); listening to music; reading blogs, books, magazines, novels or newspapers; surfing social media sites and play digital video/games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Sundqvist and Sylvén (2016), the types of EE activities that foreign language learners might be able to do include watching movies, listening to English music, reading magazines, reading books, etc. A study on the impact of using EE on English proficiency at the private university of Erbil investigated by Bala (2020) found that 87 firstyear students in English language teaching (ELT), biology education, physics education, and mathematics education often set up their mobile devices. In English as their Extramural English activity not in their native language.…”
Section: Introductionmentioning
confidence: 99%